Cultural consumption practices of visitors to the National Museum / UFRJ in social network (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article aims to understand representations of cultural consumption experiences performed by posting images on Social Networking Platforms (SNP) by lower-class individuals who visited the National Museum/UFRJ. The study was carried out employing ethnographic-inspired research, which comprised the stages of participant observation in the exhibitions, interviews with visitors, and digital observation of their publications in SNP. Among the results achieved, it is possible to highlight that the publications largely reflect practices and values that already existed before the so-called “digital life,” such as the importance of kinship and bonds of friendship in everyday relationships.
Keywords: Cultural consumption; Museums; Social networks; Low-income groups; Brazil